Improved characterization of the magnetic properties of hexagonally packed wires - Roßmanith, Hans; Albach, Manfred; Fischer, Janina; Stadler, Alexander (Epe Journal, 2011)
An improved complex permeability model for litz wire windings is derived heuristically from a comparison between simulation results and the standard analytical model. It is valid for all strand diameters, strand distances and frequencies, and may be used for accurate numerical calculations of magnetic fields and losses in magnetic components. © 2011 EPE Association - European Power Electr.
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.lselek.improv
Keywords: Conduction losses; Device simulation; Passive component; Transformer